ANALISIS KESALAHAN PENGGUNAAN –TE IRU PADA MAHASISWA ANGKATAN 2015 DAN 2016 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Kunansari Nasution, Putri Khairiah; Aibonotika, Arza; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research discusses the analysis of errors in the use of auxiliary verbs conducted by students of 2015 and 2016 of the Japanese Language Education Department, Faculty of Teacher’s Training and Education, Riau University. The purpose of this research is to find out what mistakes made by students of 2015 and 2016 of the Japanese Language Education Department, Riau University, in the use of -te iru in Japanese sentences and what factors cause errors. The method used in this research is quantitative descriptive method types. Data was obtained from the distribution of test questions and questionnaires to 30 respondents, which is 15 students from 2015 and 15 students from 2016. The results showed that the percentage of student errors in the use of –te iru was classified as quite high, amounting to 52.19%. Factors causing errors in the use of –te iru are students difficulty in understanding the use of –te iru because it is difficult to match them into native language, students only know the use of –te iru sentence patterns to express the meaning of ongoing activities, students rarely use the – te iru sentence pattern, and there are many functions and meanings that must be known so that most students are still confused in using –te iru sentence patterns such as distinguishing meanings, functions, and also having difficulty in translating.Key Words: Error analysis, te iru